A phase I pharmacokinetic and pharmacodynamic study of the oral mitogen-activated protein kinase kinase (MEK) inhibitor, WX-554, in patients with advanced solid tumours. (November 2016) - Jamieson, David; Griffin, Melanie J.; Sludden, Julieann; Drew, Yvette; Cresti, Nicola; Swales, Karen; Merriman, Mark; Allen, Rodger; Bevan, Paul; Buerkle, Markus; Mala, Carola; Coyle, Vicky; et al.
Abstract: Purpose: We performed a multi-centre phase I study to assess the safety, pharmacokinetics (PK) and pharmacodynamics (PD) of the orally available small molecule mitogen-activated protein kinase kinase (MEK) 1/2 inhibitor, WX-554, and to determine the optimal biological dose for subsequent trials. Experimental design: Patients with treatment-refractory, advanced solid tumours, with adequate performance status and organ function were recruited to a dose-escalation study in a standard 3 + 3 design. The starting dose was 25 mg orally once weekly with toxicity, PK and PD guided dose-escalation with potential to explore alternative schedules. Results: Forty-one patients with advanced solid tumours refractory to standard therapies and with adequate organ function were recruited in eight cohorts up to doses of 150 mg once weekly and 75 mg twice weekly. No dose-limiting toxicities were observed during the study, and a maximum tolerated dose (MTD) was not established. The highest dose cohorts demonstrated sustained inhibition of extracellular signal-regulated kinase (ERK) phosphorylation in peripheral blood mononuclear cells following ex-vivo phorbol 12-myristate 13-acetate stimulation. There was a decrease of 70 ± 26% in mean phosphorylated (p)ERK in C1 day 8 tumour biopsies when compared with pre-treatment tumour levels in the 75 mg twice a week cohort. Prolonged stable disease (>6 months) was seen in two patients, one with cervical cancer and one with ampullary carcinoma. Conclusions: WX-554 was well tolerated, and an optimal biological dose was established for further investigation in either a once or twice weekly regimens. The recommended phase 2 dose is 75 mg twice weekly. Highlights: A phase I study of the mitogen-activated protein kinase kinase 1/2 inhibitor, WX-554. Marked and sustained inhibition of extracellular signal-regulated kinase phosphorylation in surrogate tissue and tumour biopsy. Optimal biological dose established for further investigation in subsequent trials.